The effects of a free premium sales promotion on the attitudinal loyalty of a consumer - Geldenhuis, Dewald (My University, 2017)
Sales promotions are ever-present occurrences in modern day markets with companies using them as part of their marketing mix (Blattberg & Neslin, 1990). They also have the ability to effect customer satisfaction and in turn the brand loyalty for that consumer (Li-Xin & Shou-Lian, 2010). Bawa and Shoemaker (2004) found links between non-monetary sales promotions and the brand loyalty of a consumer. Consumers exposed to sales promotions usually had increased purchasing probability and enhanced loyalty to the brand, compared to consumers that were not exposed to the promotion. This study set out to establish the effects on the attitudinal loyalty of consumers who missed the opportunity to partake in a free premium sales promotion. Utilizing a quantitative research methodology, data was collected by means of a structured questionnaire from respondents in South Africa. Internal factors such as the consumers experience of cognitive dissonance; emotion showed towards the brand; and their attitudes towards the brand, were measured and analysed through factor analysis. The most notable finding from the study was that the effect on a consumer’s attitudinal loyalty was contained to the attitude they have towards the brand, irrespective of the level of dissonance that might appear or even the emotional feelings they might have for the brand. Missing the sales promotion would almost certainly alter their perception of the brand and change the internal factors a consumer turns to when searching for information and evaluating their post-purchase consumption. Ultimately, a missed free premium sales promotion will do very little to destroy any brand loyalty that is already present with that consumer.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Strategic Marketing Johannesburg, 2017
Keywords: Customer loyalty--South Africa; Consumer satisfaction--South Africa; Brand choice--South Africa; Sales promotion--South Africa